2021
DOI: 10.1093/pm/pnab048
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effect of Scalp Acupuncture on Pain, Sleep Disorders, and Quality of Life in Patients with Temporomandibular Disorders: A A Randomized Clinical Trial

Abstract: Background and Objective To evaluate the effects of Chinese scalp acupuncture in patients diagnosed with Temporomandibular Disorders (TMD) on pain, sleep and quality of life (QOL), and compare these results with the results from traditional therapies. Methods Sixty patients diagnosed with TMD using the Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) were allocated into four treatment groups: Counselling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…After screening, 83 articles were rejected as they did not meet the inclusion criteria for several reasons leaving 84 papers whose full text was obtained and read. After examining the full text of these 84 papers, 20 papers (19 original studies and one follow‐up report) were identified as eligible for inclusion in this systematic review: Komiyama et al, 1999 16 ; Wright et al, 2000 17 ; Carlson et al, 2001 3 ; Dworkin et al, 2002 18 ; Michelotti et al, 2004 19 ;Truelove et al, 2006 4 ; Turner et al, 2006 20 ; Mulet et al, 2007 21 ; Turner et al, 2011 22 ; Nie‐mela et al, 2012 23 ; Michelotti et al, 2012 24 ; Craane et al, 2012 25 ; De Vocht et al, 2013 26 ; Conti et al, 2015 27 ; Costa et al, 2015 28 ; Qvintus et al, 2015 29 ; Giro et al, 2016 30 ; Lam et al, 2020 31 ; De Resende et al, 2021 32 ; Peixoto et al, 2021 33 . A list of the 64 papers excluded with reasons for exclusion is available in the Appendix S3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After screening, 83 articles were rejected as they did not meet the inclusion criteria for several reasons leaving 84 papers whose full text was obtained and read. After examining the full text of these 84 papers, 20 papers (19 original studies and one follow‐up report) were identified as eligible for inclusion in this systematic review: Komiyama et al, 1999 16 ; Wright et al, 2000 17 ; Carlson et al, 2001 3 ; Dworkin et al, 2002 18 ; Michelotti et al, 2004 19 ;Truelove et al, 2006 4 ; Turner et al, 2006 20 ; Mulet et al, 2007 21 ; Turner et al, 2011 22 ; Nie‐mela et al, 2012 23 ; Michelotti et al, 2012 24 ; Craane et al, 2012 25 ; De Vocht et al, 2013 26 ; Conti et al, 2015 27 ; Costa et al, 2015 28 ; Qvintus et al, 2015 29 ; Giro et al, 2016 30 ; Lam et al, 2020 31 ; De Resende et al, 2021 32 ; Peixoto et al, 2021 33 . A list of the 64 papers excluded with reasons for exclusion is available in the Appendix S3.…”
Section: Resultsmentioning
confidence: 99%
“…Sixteen of the studies used pain intensity as an outcome measure and it was measured using: the visual analogue scale (VAS) in nine studies 3,16,19,23–25,27,32,33 ; the characteristic pain intensity scale (CPI) in three studies 18,20,22 ; a numerical rating scale (NRS) in two studies 21,26 ; the symptom severity index (SSI) in one study 17 ; and the graded chronic pain scale (GCPS) in one study 31 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We required the nursing staff to formulate a scientific and reasonable nursing plan before implementing nursing interventions to have a clear understanding of the nursing content according to the patient's condition, needs, and disease risk assessment [24]. Patients with TMD lack awareness of the disease, and its complications may bring negative emotions such as anxiety and depression [25][26][27]. Psychological counseling for patients showed that individualized nursing could improve patients' anxiety and depression.…”
Section: Discussionmentioning
confidence: 99%